A new system for classifying root and root canal morphology. (17th October 2016) - Ahmed, H. M. A.; Versiani, M. A.; De‐Deus, G.; Dummer, P. M. H.
Abstract: Knowledge of root and root canal morphology is a prerequisite for effective nonsurgical and surgical endodontic treatments. The external and internal morphological features of roots are variable and complex, and several classifications have been proposed to define the various types of canal configurations that occur commonly. More recently, improvements in nondestructive digital image systems, such as cone‐beam and micro‐computed tomography, as well as the use of magnification in clinical practice, have increased the number of reports on complex root canal anatomy. Importantly, using these newer techniques, it has become apparent that it is not possible to classify many root canal configurations using the existing systems. The purpose of this article is to introduce a new classification system that can be adapted to categorize root and root canal configurations in an accurate, simple and reliable manner that can be used in research, clinical practice and training.